Toward the institutionalization of quantum computing in pharmaceutical research. Issue 2 (February 2022) - Zinner, Maximillian; Dahlhausen, Florian; Boehme, Philip; Ehlers, Jan; Bieske, Linn; Fehring, Leonard
Highlights: Domain experts of 12 large pharma companies provide their perspectives on QC. QC's scientific potential may not translate into unprecedented investment return. To institutionalize QC, education, collaborations and use cases need to be tackled. Management commitment and organizational culture required to institutionalize QC. Abstract: Innovative pharmaceutical companies have started to explore quantum computing (QC). In this article, we provide a collective industry perspective from QC domain leaders at leading pharmaceutical companies. There are immediate nonfinancial benefits in engaging with QC, some likely financial returns in the short term in drug development, manufacturing, and supply chain, and potentially large scientific benefits in drug discovery long term. We discuss the required activities for institutionalizing QC: how to create an understanding of QC among researchers and management, which and how to deploy external resources, and how to identify the problems to be addressed with QC. If (and once) deployable, QC will likely have a similar trajectory to that of computer-aided drug design (CADD) and artificial intelligence (AI) during the 1990s and 2010s, respectively.